2016
DOI: 10.1177/1557988316635247
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With HIV Testing Among Men in Haiti: Results From the 2012 Demographic and Health Survey

Abstract: HIV testing serves as the gateway to HIV prevention and treatment. However, little is known about the correlates of HIV testing among men in the Caribbean. The Anderson Behavioral Model was used to examine factors associated with HIV testing among 7,354 men who participated in the 2012 Demographic and Health Survey conducted in Haiti. Few men (35%) reported having ever been tested for HIV. Logistic regression analyses revealed that HIV testing increased with education and wealth. Marital status was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 31 publications
10
23
2
Order By: Relevance
“…We also elicited their recommendations for how to implement both primary HIVST distribution and secondary distribution of HIVST for male partners of Option B+ clients in the country. This article builds on previous quantitative research assessing factors associated with HIV testing among men [48] and HIV status disclosure to sexual partners among adult men and WLWH in Haiti [49]. The findings will help to inform future implementation and scaling up of HIVST to increase HIV testing among heterosexual men in Haiti.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We also elicited their recommendations for how to implement both primary HIVST distribution and secondary distribution of HIVST for male partners of Option B+ clients in the country. This article builds on previous quantitative research assessing factors associated with HIV testing among men [48] and HIV status disclosure to sexual partners among adult men and WLWH in Haiti [49]. The findings will help to inform future implementation and scaling up of HIVST to increase HIV testing among heterosexual men in Haiti.…”
Section: Introductionmentioning
confidence: 90%
“…The persistently high levels of the adult population who have never tested for HIV and the disparity between men and women are concerning for HIV testing and initiation of antiretroviral therapy (ART) [3]. Evidence from a nationally representative sample of heterosexual men demonstrated that condomless sex is high [4] and that HIV testing is associated with less condomless sex [5], indicating the importance of promoting HIV testing among men.…”
Section: Introductionmentioning
confidence: 99%
“…Though HIV testing has served as a cornerstone in the fight against the HIV epidemic, testing uptake has consistently remained lower among men than women in several parts of the world, including sub-Saharan Africa ( Abongomera et al, 2015 ; Asaolu et al, 2016 ; Brima et al, 2015 ; Carrasco, Fleming, Wagman, & Wong, 2018 ; Conserve et al, 2013 ; Conserve et al, 2017 ; Johnson, Rehle, Jooste, & Bekker, 2015 ; Takarinda et al, 2016 ). In Tanzania, for example, only 47% of men compared to 62% of women have ever been tested for HIV ( TACAIDS & NBS OCGS, 2013 ).…”
mentioning
confidence: 99%
“…HIV testing rates were examined in 10 studies 21–30. In Barbados, the number of people tested increased significantly from 14 403 tests completed in 2000 to 26 045 in 2010 22. Of 7354 men in Haiti, 65.24% (n=4838) had not been tested for HIV 22.…”
Section: Resultsmentioning
confidence: 99%
“…In Barbados, the number of people tested increased significantly from 14 403 tests completed in 2000 to 26 045 in 2010 22. Of 7354 men in Haiti, 65.24% (n=4838) had not been tested for HIV 22. In Puerto Rico, 59% of MSM had received a recent HIV test 23.…”
Section: Resultsmentioning
confidence: 99%